Analisis LKPD dan Alat Ukur Sederhana Kapasitas Paru-paru dalam Mengembangkan HOTS (Higher Order Thinking Skills) - Minnathul Khasanah; Bambang Supriatno; Sri Anggraeni (Bioscientist : Jurnal Ilmiah Biologi, 2021)
Student Worksheet (LKPD) is a practical guide in science learning. The existence of LKPD makes practicum activities can be carried out properly and structured. However, in biology lessons, especially the LKPD of the human respiratory system, the practicum of measuring lung capacity in the field is still not appropriate. Therefore, this study aims to reconstruct the LKPD on the human respiratory system material about practicum measuring lung capacity. This research uses the ANCOR (Analysis, Trial, and Reconstruction) stages. This study uses a quantitative descriptive method. The sample in this study amounted to 8 samples of LKPD selected using purposive sampling technique. The instrument used consists of 3 components, including: conceptual analysis, analysis of knowledge construction based on the Vee Diagram adapted from Novak and Gowin (1984), and practical analysis. The results showed that there were still various problems in conceptual analysis, knowledge construction analysis, and practical analysis. In addition, the results of trials related to practicum measuring lung capacity there are still unclear work procedures, as well as practicum tools used to measure lung capacity have weaknesses and are less accurate in data acquisition. So that there is a need for a better LKPD reconstruction, constructing student knowledge, and in accordance with the basic competencies in the applicable curriculum. Meanwhile, to overcome the weakness of the practicum tool, the researchers made an alternative simple tool to measure lung capacity that can develop the HOTS ability of students.